2016
DOI: 10.1007/s10661-016-5403-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic extreme values modeling and monitoring by means of sea shores water quality biomarkers and valvometry

Abstract: Water quality can be evaluated using biomarkers such as tissular enzymatic activities of endemic species. Measurement of molluscs bivalves activity at high frequency (e.g., valvometry) during a long time period is another way to record the animal behavior and to evaluate perturbations of the water quality in real time. As the pollution affects the activity of oysters, we consider the valves opening and closing velocities to monitor the water quality assessment. We propose to model the huge volume of velocity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In Durrieu et al (2015) and Durrieu et al (2016), we observe that valvometry using extreme value theory allows in real-time in situ analysis of the bivalve behavior and appears as an effective early warning tool in ecological risk assessment and marine environment monitoring.…”
Section: Sea Shores Water Qualitymentioning
confidence: 95%
See 1 more Smart Citation
“…In Durrieu et al (2015) and Durrieu et al (2016), we observe that valvometry using extreme value theory allows in real-time in situ analysis of the bivalve behavior and appears as an effective early warning tool in ecological risk assessment and marine environment monitoring.…”
Section: Sea Shores Water Qualitymentioning
confidence: 95%
“…u-bordeaux1.fr/. High-frequency data (10 Hz) are produced by noninvasive valvometric techniques and the study of the bivalve's behavior in their natural habitat leads to the proposal of several statistical models (Sow, Durrieu, and Briollais 2011;Schmitt et al 2011;Jou and Liao 2006;Coudret, Durrieu, and Saracco 2015;Azaïs, Coudret, and Durrieu 2014;Durrieu et al 2015Durrieu et al , 2016. It is observed that in the presence of a pollutant, the activity of the bivalves is modified and consequently they can be used as bioindicators to detect perturbations in aquatic systems (pollutions, global warming).…”
Section: Sea Shores Water Qualitymentioning
confidence: 99%
“…Several monitoring and early warning systems, based on valvometry measurements, have been described in the literature (e.g., [8,23,[45][46][47][48][49], see also Table A2); additionally, a few systems have been commercialized (Table A1). The system that we proposed in this study is, to the best of our knowledge, the first to be built on a biophysical model of the adductor muscle dynamics.…”
Section: A System Based On Quantification Of the Valve Gape Dynamicsmentioning
confidence: 99%
“…As argued in Ahmed et al 2015and Durrieu et al 2016, pollution can affect the activity of oysters and in particular the shells opening and closing velocities and so the movement speeds can be considered as an indicator of the animal stress activity since its movements are associated to aquatic system perturbations. In Ahmed et al 2015, the authors propose an interesting deterministic alternative method for the estimation of movement velocity based on differentiator estimators.…”
Section: High-frequency Valvometry Datamentioning
confidence: 99%